PLACENTAL SECRETORY FACTORS INFLUENCE TO THP-1 CELLS PHENOTYPE AND THP-1 CELLS TRANSENDOTHELIAL MIGRATION - O. I. Stepanova; G. R. Kozonov; D. Z. Tsitskarava; T. U. Kuzminykh; D. A. Korenkov; S. A. Selkov; D. I. Sokolov (Медицинская иммунология, 2014)
Decidual and placental macrophage pools are renewed due to its transendothelial monocyte migration from peripheral blood. Tissue macrophages control placental development and provide fetomaternal immunological tolerance. Preeclamptic pregnancy is accompanied by increased monocyte migration to decidual tissue and local inflammatory events. Regulatory mechanisms of monocyte recruitment to placental and decidual tissues is still unclear. Therefore we investigated the influence soluble placental factors (SPFs) during the first- and third-trimester normal pregnancy, as compared to effects of these factors in preeclamptic pregnancy. We studied biological actions of SPF upon transendothelial migration of monocyte-like THP-1 cells and their phenotypic pattern. Transendothelial migration of THP-1 cells was more intensive with firsttrimester SPFs from normal pregnancy, when compared with third-trimester samples, and it was accompanied by decreased CD11a expression. SPFs from pre-eclamptic pregnancy caused an increase in transendothelial migration of THP-1 cells, as compared to SPFs from normal pregnancies, being accompanied by increased CD11b expression. The present study was supported by grants ГК №  02.740.11.0711, НШ-3594.2010.7, МД-150.2011.7 and a grant from St.-Petersburg Goverment for young scientists.